Three generations - Elliott, Maud Howe, 1854-1948 (Salt Lake City, UT : Project Gutenberg, 2022)
"Three Generations" by Maud Howe Elliott is an autobiographical narrative written in the early 20th century. This work reflects on the author$1 (Bs life experiences and family heritage, particularly focusing on her childhood in a prominent Boston family known for its intellectual and cultural connections. The book provides insight into the lives of significant historical figures and events that shaped the author's formative years. The opening of "Three Generations" introduces us to the author as she reflects on her life in the context of significant friendships and familial bonds. Set in 1916, the narrative begins with the announcement of Henry James's death, prompting her to consider her own life$1 (Bs recollections and the importance of preserving memories. We learn about her early childhood, including her birth at the Perkins Institution for the Blind, which was established by her father, and the deep connections she had with her family members, including significant figures like her mother, Julia Ward Howe, and prominent friends like Theodore Parker and John Brown. These memories create a vivid backdrop of her family$1 (Bs influence amidst a rich tapestry of social and cultural interactions, ultimately setting the stage for a reflective journey through her early life experiences. (This is an automatically generated summary.)s
The twilight of the gods -- The owls -- Green peace -- Schools and teachers -- Uncle Sam Ward -- A stay at the White House -- Santo Domingo -- Newport -- Some painters and poets -- England -- Rome -- Egypt, Palestine, Greece -- Boston in the eighties -- The New Orleans Cotton Centennial -- Chicago and Boston in the nineties -- London in the nineties -- Arabian days -- Artist life in Rome, 1894 -- A year of travel -- My mother's last Roman winter -- Queen Margherita at our studio -- By the Tiber and by the Charles -- Washington in 1910 -- Theodore Roosevelt and the Progressive Party -- The Art Association of Newport.
Release date is 2022-08-21
Chuck Greif and the Online Distributed Proofreading Team at http://www.pgdp.net (This file was produced from images available at The Internet Archive)
Keywords: Autobiographies; Elliott, Maud Howe, 1854-1948